Biomarkers for Duchenne muscular dystrophy: myonecrosis, inflammation and oxidative stress - Miranda D. Grounds; Jessica R. Terrill; Basma A. Al-Mshhdani; Marisa N. Duong; Hannah G. Radley-Crabb; Peter G. Arthur (The Company of Biologists, 2020)
Duchenne muscular dystrophy (DMD) is a lethal, X-linked disease that causes severe loss of muscle mass and function in young children. Promising therapies for DMD are being developed, but the long lead times required when using clinical outcome measures are hindering progress. This progress would be facilitated by robust molecular biomarkers in biofluids, such as blood and urine, which could be used to monitor disease progression and severity, as well as to determine optimal drug dosing before a full clinical trial. Many candidate DMD biomarkers have been identified, but there have been few follow-up studies to validate them. This Review describes the promising biomarkers for dystrophic muscle that have been identified in muscle, mainly using animal models. We strongly focus on myonecrosis and the associated inflammation and oxidative stress in DMD muscle, as the lack of dystrophin causes repeated bouts of myonecrosis, which are the key events that initiate the resultant severe dystropathology. We discuss the early events of intrinsic myonecrosis, along with early regeneration in the context of histological and other measures that are used to quantify its incidence. Molecular biomarkers linked to the closely associated events of inflammation and oxidative damage are discussed, with a focus on research related to protein thiol oxidation and to neutrophils. We summarise data linked to myonecrosis in muscle, blood and urine of dystrophic animal species, and discuss the challenge of translating such biomarkers to the clinic for DMD patients, especially to enhance the success of clinical trials.